Q: 18 plus 19 plus 42 plus 26 equals?

Write your answer...

Submit

Related questions

112

-3.........

-1

If: 26 = 8+v Then: v = 18

26 = 8 + v V = 26 - 8 = 18

8 + 6f = 26 Therefore, 6f = 18 f = 18/6 f = 3

-8 + 10x = 18 10x = 18+8 10x = 26 x = 26/10 x = 2.6

19 + (-2) + (-26) = -9

2n + 19 = -7 2n = -7 - 19 2n = -26 n= -13

19+-26 = 19 - 26 = -7

13+13=26

15x26=390

19 - 2 - 26 = - 9

26! Why can't you put 4 into the x? x=4 2x+18 (2*4)+18 8+18= 26

How about 20 plus 6 equals 26 as one example

-26

8 + 3(6) = 8 + 18 = 26

26 + 8 = 34

n = 26

19 + 7 = 26

7 + 19 = 26

20 + 7 7 + 20 8 + 19 19 + 8 9 + 18 18 + 9 10 + 17 17 + 10 11 + 16 16 + 11 15 + 12 12 + 15 14 + 13 13 +14

26

38 * 2 = 76 19 * 4 = 76

18 26 33 19 27 34 20 28 35 ....